(untitled) (Nigerian Journal of Physiological Sciences, 2025)
The worldwide obesity epidemic presents a considerable public health and economic challenge globally. While lifestyle and genetic predisposition are recognized obesogenic factors, compelling evidence indicates that maternal nutritional "insults" (MNI) occurring before pregnancy, during pregnancy, or during lactation predispose the offspring to obesity and other cardiometabolic disorders in adulthood. This phenomenon termed developmental origins of health and disease (DOHaD) can be utilized to formulate intervention strategies aimed at counteracting the developmental programming of obesity in subsequent generations. The placenta, a temporary organ of pregnancy, experiences adaptive changes in response to MNI. Alterations in placental secretory functions, morphology, and gene expression profiles influence foetal metabolic pathways. The mechanisms through which placental adaptations influence developmental programming present a distinct opportunity to pinpoint targets in combating the increasing prevalence of obesity. Clinical and experimental studies have clarified various underlying mechanisms, including modified placental metabolic regulation, oxidative stress, inflammation, immune dysregulation, and epigenetic alterations, offering insights for the formulation of effective intervention strategies. This review encapsulates placental adaptive responses to MNI, elucidates the underlying mechanisms, explores potential placental intervention strategies, and identifies areas for future research.